The European Blood and Marrow Transplantation Textbook for Nurses Under the Auspices of EBMT - Kenyon, Michelle; Babic, Aleksandra (Springer Nature, 2018)
Haematopoietic Stem Cell Transplant; Nursing care; Haemato-oncology nursing; Paediatric transplant nursing; Apheresis